Kecerdasan Spiritual, Subjective Well-Being Dan Tingkat Pendidikan Sebagai Prediktor Kesadaran Lingkungan Pada Masyarakat Di Sekitar Danau Tondano - Ruata, Shanti N.Ch; Andrias, Juan Wideni Candra; Sensanen, Emilia Alci (PT. Giat Konseling Nusantara, 2024)
The responsibility of the community around Lake Tondano to protect and maintain the environment around the lake, amid the threat of community indifference and government programs in cleaning water hyacinth and infrastructure projects and fisheries carried out around the lake threatens this natural sustainability. The purpose of this study is to determine whether spiritual intelligence, subjective well-being and education level are predictors of environmental awareness in the community around Lake Tondano. The research method used is quantitative method with multiple linear regression test analysis with the help of SPSS. The population is the community around Lake Tondano with the sample is the community in Eris sub-district. The results showed that spiritual intelligence, subjective well-being and education level can be used as predictors of environmental awareness in the community around Lake Tondano, with the results of an analysis of 42% of the influence given by these three variables on environmental awareness, the rest are variables not examined in this study.